2020
DOI: 10.1073/pnas.1912146117
|View full text |Cite
|
Sign up to set email alerts
|

A hepatocyte differentiation model reveals two subtypes of liver cancer with different oncofetal properties and therapeutic targets

Abstract: Clinical observation of the association between cancer aggressiveness and embryonic development stage implies the importance of developmental signals in cancer initiation and therapeutic resistance. However, the dynamic gene expression during organogenesis and the master oncofetal drivers are still unclear, which impeded the efficient elimination of poor prognostic tumors, including human hepatocellular carcinoma (HCC). In this study, human embryonic stem cells were induced to differentiate into adult hepatocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 49 publications
2
38
0
Order By: Relevance
“…For example, the production of catalytically impaired splice variants of the nucleotide-regulating enzymes ecto-5 0nucleotidase (NT5E) 35 and kynurenine formamidase (AFMID) 36 occurs only in humans. In light of that, the most effective strategies for identifying tumor-promoting oncofetal splice variants and mechanisms can come out of integrating data from human HCC cell-based models 64,65 and tissue specimens 66 with the most appropriate animal models. [67][68][69] Up-regulation of the Oncofetal Splicing Factor Muscleblind-Like 3 in HCC Muscleblind-like (MBNL) proteins are encoded by 3 genes (MBNL1-3) and regulate RNA splicing in a tissuespecific manner.…”
Section: Alternative Splicing In Liver Development and Maturationmentioning
confidence: 99%
“…For example, the production of catalytically impaired splice variants of the nucleotide-regulating enzymes ecto-5 0nucleotidase (NT5E) 35 and kynurenine formamidase (AFMID) 36 occurs only in humans. In light of that, the most effective strategies for identifying tumor-promoting oncofetal splice variants and mechanisms can come out of integrating data from human HCC cell-based models 64,65 and tissue specimens 66 with the most appropriate animal models. [67][68][69] Up-regulation of the Oncofetal Splicing Factor Muscleblind-Like 3 in HCC Muscleblind-like (MBNL) proteins are encoded by 3 genes (MBNL1-3) and regulate RNA splicing in a tissuespecific manner.…”
Section: Alternative Splicing In Liver Development and Maturationmentioning
confidence: 99%
“…Some studies have attempted to induce hepatocytes from several sources, such as embryonic, fetal, and somatic stem cells, by recapitulating the pathways controlling liver development 15,16 . Here, we reported that definitive endoderm (DE), liver progenitor (LP) cells, and premature hepatocytes (PH) could be induced from human embryonic stem (ES) cells by treating cell cultures with certain concentrations of factors 17 . By deep RNA sequencing, we characterized molecular signatures of liver progenitor cells and premature hepatocytes, which may be important to HCC development.…”
mentioning
confidence: 99%
“…Increasing evidences suggested that the hierarchy of cancer stem cells and their differentiated progenies contributed substantially to the heterogeneous tumor and therapeutic failure [ 4 , 5 ]. To better understand the dynamic transcriptomic change during liver development, we have recently established a hepatocyte differentiation model, which specifically induced human embryonic stem cells (hESCs) to differentiate into mature hepatocytes along hepatic lineages [ 6 ]. Meanwhile, liver tumors were inoculated into immune deficient mice and treated with Sorafenib to establish a drug resistant model.…”
Section: Main Textmentioning
confidence: 99%